Discussion of An Empirical Study of the Role of Accounting Data in Performance Evaluation - Martin, R. W. (Journal of Accounting Research, 1972)
R. W. Martin, Discussion of An Empirical Study of the Role of Accounting Data in Performance Evaluation, Journal of Accounting Research, Vol. 10, Empirical Research in Accounting: Selected Studies 1972 (1972), pp. 187-188